Depression and its Main Determinants Among Iranian Operating Room Personnel: A Systematic Review and Meta-Analysis - Ameri, Mehdi; Hosseini Nodoushan, Mohammad Reza; Shahbazzadeh, Amir; Arab Ahmadi, Mehran (International Clinical Neuroscience Journal, 2018)
Background: Most nurses, especially operating room personnel, seems to be more likely to be affected by mood disorders than other social strata. The present study attempted to systematically review the prevalence of depression and its main determinants among operating room personnel in Iran. Methods: The method of this systematic review is documenting in a published protocol in the International Prospective Register of Systematic Reviews (PROSPERO) and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist. After this massive search, titles and abstracts of retrieved documents have screened and all irrelevant articles excluded. Two reviewers screened the documents and selected all relevant studies and assessed included articles separately. Results: Totally, 12 citations found in the initial literature search where four citations excluded, as they did not meet the inclusion criteria. The final number of studies available for analysis was 12 including a total of 373 operating room personnel (86 men and 287 women, mean the age of 27.71 years ranged from 20 to 36 years). The pooled prevalence of depression among operating room personnel was estimated to be 45.3%. In this regard, 27.0% of personnel suffered from severe depression. A significant heterogeneity found in the overall analysis of the overall prevalence of depression and its severe pattern. Conclusion: A notable number of operating room personnel in Iran suffer from depression even in its severe condition emphasizing the importance of the managerial approach to minimize its adverse effects on their performance as well as to improve their quality of life.